Design Implementation of Search Engine Optimization (SEO) in MSMEs - Rahadi, Putu Suta Adya Dharma; Wiharta, Dewa Made; Saputra, Komang Oka (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The rapid development of web and internet technology today allows someone to make the desired website easier. But the fact is that after creating a website, many things must be done by someone so that their online business can make a profit. One of them is Search Engine Optimization. In this study, we will discuss website design that uses  Search Engine Optimization for MSMEs, where there are factors such as internal and external to maximize website design. The use of SEO can help MSMEs increase traffic to the website, helping to choose focus keywords, page titles, and meta descriptions that suit their needs. This can be seen from google analytics installed and gets data on changes from before and after the website implements SEO. Based on the study results, it can conclude that the design of the implementation of search engine optimization in MSMEs has been successfully carried out.